Performance Analysis for MIMO LTE on the High Altitude Platform Station - Catur Budi Waluyo; Yenni Astuti (Proceeding of the Electrical Engineering Computer Science and Informatics, 2017)
High Altitude Platform Station (HAPs) is a new communications infrastructure that uses air balloon to carry high data rate service and wide bandwidth. One technique to make it happen is Long Term Evolution (LTE), LTE support capacity increasing, expand coverage area, data rate increasing, multi- antenna, and can be integrated with other systems. To improve the performance of LTE in capacity building, coverage area, and data rate, it can use the multi-antenna techniques both on receiver or transmitter or often called multiple input multiple outputs (MIMO). Type of MIMO technique in this paper is spatial Multiplexing. In this study, an estimation that has been used is the Linear Minimum Mean Square Error (LMMSE). Channel estimation is used to find out information about the channel condition between the transmitter and the receiver so that the performance of Bit Error Rate (BER) increase and expand the coverage area of the same BER compared without estimation. The system performed channel estimation has a better performance than the without estimation system with improved SNR of 20dB. Based on the simulation to get the same BER value in the system with channel estimation and without estimation, on the system with estimation it is necessary to lower elevation angle to be 10° and still there was improvement of SNR of 3 dB compared to the system without any estimation. With lowered elevation angle from  90° to 10°, the area of coverage was greater becomes 215.77km from the original 0.032km